Atributos estruturais e mineralógicos em classes de solos na chapada do apodi - Lopes, Thais Cristina de Souza (2018)
Soil structure plays essential roles in plant growth factors in agroecosystems. The objective of the present work was to evaluate structural attributes in association with physical, chemical and mineralogical properties in soil classes, using the multivariate statistical technique in the differentiation of environments. The research was carried out in the Terra da Esperança Settlement Project, in the municipality of Governador Dix-Sept Rosado, and in the Moacir Lucena Settlement Project, in Apodi, in the state of Rio Grande do Norte. 17 profiles were selected in different agroecosystems. Soil samples were collected in the horizons of each profile, the undisturbed constituted 10 samples per horizons in volumetric rings, in soil blocks (aggregate analysis), and the deformed in triplicates in the laboratory. Structural, physical, chemical and mineralogical attributes were determined. The results were analyzed by subjecting them to multivariate statistical techniques, through correlation matrix, clustering analysis and factorial analysis with factor extraction in main components. The factorial analysis revealed that the variables clay, Ca2+, Na+, sum of bases (SB) and saturation by bases (V) for factor 1 (F1), followed by the variables cation exchange capacity (CEC), total organic carbon (TOC), macroporosity, particle density (Dp), K+ and microporosity (F2) were sensitive attributes in the distinction of the environments for the two study areas. The use of cluster analysis allowed the formation of four groups of soils, the structural ones showed greater similarity, evidencing the relationships between the source material and the uses, followed by the chemicals P, K+, T, Ca+2, V and pH (Chernossolo Rêndzico), AGRI> 2mm, plasticity index (PI), and plasticity limit (PL) (Latossolo Vermelho amarelo) and physical-chemical conductivity (Ptcalc), saturation by aluminum (m), total sand (Sands Tot.), volumetric moisture (θ), Mg+2 and Dp (Cambissolos Háplicos e Neossolo Flúvico) to Governor Dix-Sept Rosado area. The clay fraction presented an interrelation with the chemical attributes (F1), in the distinction of classes and uses. The soil classes under study presented a eutrophic character (V≥ 50%), including the Latossolo Vermelho-Amarelo (Profile 4) as a function of the Na+ and Ca2+ variables, but presented lower values than the other classes, which is a local peculiarity, according to the climatic pattern of the semi-arid region. In relation to the mineralogical characterization, F1 allowed to estimate the influence of the expressive variables, such as: clay, Fe extracted with dithionite-citrate bicarbonate (Fed), Fe ratio extracted with ammonium acid oxalate and sodium dithionite-citrate bicarbonate (Feo/Fed), microporosity, macroporosity and Na+, this can be justified by the factors and pedogenetic processes that are strongly influenced by the climatic pattern of the semi-arid region. The most developed soils showed evident peaks of silicate minerals (kaolinite and illite) and iron oxides (goethite and hematite). The group characterized as less developed soils presented peaks of lower kaolinite intensity, with the most evident presence of 2:1 type clay minerals